Investigating ongoing brain oscillations and their influence on conscious perception – network states and the window to consciousness - Ruhnau, Philipp; Hauswald, Anne; Weisz, Nathan (Frontiers in Psychology, 2014)
In cognitive neuroscience, prerequisites of consciousness are of high interest. Within recent years it has become more commonly understood that ongoing brain activity, mainly measured with electrophysiology, can predict whether an upcoming stimulus is consciously perceived. One approach to investigate the relationship between ongoing brain activity and conscious perception is to conduct near-threshold (NT) experiments and focus on the pre-stimulus period. The current review will, in the first part, summarize main findings of pre-stimulus research from NT experiments, mainly focusing on the alpha band (8-14 Hz). It is probable that the most prominent finding is that local (mostly sensory) areas show enhanced excitatory states prior to detection of upcoming NT stimuli, as putatively reflected by decreased alpha band power. However, the view of a solely local excitability change seems to be too narrow. In a recent paper, using a somatosensory NT task, Weisz et al. (2014) replicated the common alpha finding and, furthermore, conceptually embedded this finding into a more global framework called ‘Windows to Consciousness’ (Win2Con). In this review, we want to further elaborate on the crucial assumption of ‘open windows’ to conscious perception, determined by pre-established pathways connecting sensory and higher order areas. Methodologically, connectivity and graph theoretical analyses are applied to source-imaging magnetoencephalographic data to uncover brain regions with strong network integration as well as their connection patterns. Sensory regions with stronger network integration will more likely distribute information when confronted with weak NT stimuli, favoring its subsequent conscious perception. First experimental evidence confirms our aforementioned ‘open window’ hypothesis. We therefore emphasize that future research on prerequisites of consciousness needs to move on from investigating solely local excitability to a more global view of network connectivity.